KOMUNIKASI MITIGASI BENCANA: Studi Kasus Mitigasi Bencana Badan Penanggulangan Bencana Daerah Provinsi Jabar dalam Menghadapi Bencana Alam Gempa Bumi Akibat Sesar Lembang - Iqbal, Mochamad; Rahiem, Vikry Abdullah; Fitrananda, Charisma Asri; Yusuf, Yogi Muhammad (Linimasa : Jurnal Ilmu Komunikasi, 2021)
This study aims to analyze the government's disaster mitigation communication in this case the Regional Disaster Management Agency (BPBD) of west Java Province in the face of earthquakes caused by the Lembang fault. This research was conducted using qualitative research method. The research approach is a case study, using Haddow's theory of disaster communication strategy. As the subject of his research is the Regional Disaster Management Agency of West Java Province (BPBD Jabar). This research data was obtained through in-depth interviews and Library studies. The results showed that disaster mitigation communication conducted by the Regional Disaster Management Agency of West Java Province (BPBD Jabar) has not been carried out to the maximum because it is not a top priority so it does not have a clear pattern in disaster mitigation communication, although it has held mitigation programs such as: 1. Socialization of disaster risk areas 2. Disaster response training 3. Installation of Road Maps and Evacuation Signs assisted by the community / disaster volunteers. 4. Create educational media for school children (video animation). 5. establish a disaster preparedness village. These programs have not been conducted intensively plus BPBD Jabar itself does not have a disaster mitigation communication team that focuses on providing understanding to the community regarding the risk of earthquake disasters due to the fault of lembang.